2015
DOI: 10.1007/s10984-015-9197-y
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a Supportive Learning Environment for Expertise Development Questionnaire (SLEED-Q)

Abstract: Development of professional expertise is the process of continually transforming the repertoire of knowledge, skills and attitudes necessary to solve domainspecific problems which begins in late secondary education and continues during higher education and throughout professional life. One educational goal is to train students to think more like experts and approach the mastery of a subject as an expert would. Helping students to develop professional expertise and evaluating whether classrooms are conducive to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 58 publications
1
7
0
1
Order By: Relevance
“…The findings describe how WBHE can contribute to the development of professional expertise and higher level of learning. Consistent with earlier research on expertise and professional learning (e.g., Cheetham and Chivers 2001;Elvira et al 2016;Grenier 2009), our review confirms that expertise is developed through transforming and integrating theoretical, practical and self-regulative knowledge. According to the review, this can be achieved by offering professionals multiple opportunities for problem solving, reflection, learning from errors and boundary crossing.…”
Section: Discussionsupporting
confidence: 89%
“…The findings describe how WBHE can contribute to the development of professional expertise and higher level of learning. Consistent with earlier research on expertise and professional learning (e.g., Cheetham and Chivers 2001;Elvira et al 2016;Grenier 2009), our review confirms that expertise is developed through transforming and integrating theoretical, practical and self-regulative knowledge. According to the review, this can be achieved by offering professionals multiple opportunities for problem solving, reflection, learning from errors and boundary crossing.…”
Section: Discussionsupporting
confidence: 89%
“…The direct experience through field observation has motivated the students to further delve the indigenous knowledge grows in a certain community. This is parallel with Elvira et al (2016) that knowledge emerging from the living environment has its own uniqueness so it creates curiosity for those who want to reveal it.…”
Section: Agree Positivementioning
confidence: 96%
“…This is justified by the fact that companies have incentives to engage in a partnership approach by adopting socially responsible activities, including environmental disclosure in a detailed and informative manner. In the same vein, Elvira et al (2016) found a positive relationship between social responsibility and the quality of disclosed information, in which the latter is conditioned by the existence of the former. They argue that engagement in CSR practices must lead to some results in the area of sustainability and conclude that increased disclosure is one of those practices.…”
Section: The Effect Of Corporate Social Responsibility On Environmental Disclosurementioning
confidence: 80%
“…This work is conceived as an extension of this research topic by trying to document and formulate a conclusion on the fundamental role of the social and ethical practices in improving the environmental disclosure process. In this regard, previous studies emphasized that ethical behavior and CSR can provide mechanisms to mitigate the asymmetry of information (Elvira et al , 2016; Retief et al , 2016). As our results indicate, a higher commitment to socially responsible practices and greater use of ethical behavior seems to contribute to more effective environmental disclosure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation